Evaluation of the use of intra-operative radiology for open placement of lag screws for the stabilization of sacroiliac luxation in cats - Silveira, Francisco; Quinn, Robert J.; Adrian, Anna M.; Owen, Martin R.; Bush, Mark A. (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: To assess the effect of intra- operative radiology on the quality of lag screw insertion for the management of sacroiliac joint luxations in cats.Methods: In this retrospective single-centre study, the surgical, anaesthetic and imaging records of 40 screws (32 cats) placed with lag effect for management of sacroiliac luxation were reviewed. Postoperative radio-graphs were assessed for sacroiliac joint reduction, screw position, and sacral width purchased by each screw. Cases were divided into two groups according to the use of (IOR) or the absence of intra-operative radiology (NIOR).Results: A total of 23 lag screws were placed with the aid of intra-operative radiology and 17 without. Three of the 23 screws placed in the IOR group exited the sacrum as opposed to eight of 17 screws in the NIOR group (p = 0.03). Mean sacral width purchased by the screws in the IOR group (70.8%) was also significantly higher (p = 0.002) than in the NIOR group (54.6%). Mean general anaesthetic times for unilateral and bilateral screw placement for the IOR group and NIOR group were not significantly different.Clinical significance: The use of intra-operative radiology can significantly improve the quality of lag screw insertion for the stabilization of sacroiliac luxations in cats, which should lead to a reduced incidence of postoperative screw loosening.
Keywords: Sacroiliac luxation; lag screw; intra-operative radiology; cat